HIV-related research in correctional populations: now is the time. - Rich, Josiah D; Wohl, David A; Beckwith, Curt G; Spaulding, Anne C; Lepp, Nathaniel E; Baillargeon, Jacques; Gardner, Adrian; Avery, Ann; Altice, Frederick L; Springer, Sandra (Current HIV/AIDS reports, 2011)
The incarcerated population has increased to unprecedented levels following the 1970 US declaration of war on illicit drug use. A substantial proportion of people with or at risk for HIV infection, including those with substance use and mental health disorders, have become incarcerated. The overlapping epidemics of incarceration and HIV present a need for academic medical centers to collaborate with the criminal justice system to improve the health of incarcerated populations. With coordinated collaboration and new programmatic initiatives it is possible to reduce HIV-associated risk behaviors and the likelihood of acquisition and transmission of HIV. Centers for AIDS Research (CFAR), funded by the National Institutes of Health, have proactively responded to this need through Collaboration on HIV in Corrections (CHIC) to improve the diagnosis, treatment, linkage to care, and prevention of HIV. This collaboration serves as a model for aligning academic expertise with criminal justice to confront this challenge to individual and public health. This is especially relevant given recent evidence of the effectiveness of antiretroviral therapy in reducing HIV transmission.
Keywords: Biomedical Research; HIV Infections; Humans; Prisoners